Α-Fe2O3 concave and hollow nanocrystals: top-down etching synthesis and their comparative photocatalytic activities. Issue 10 (15th February 2016) - Li, Pengwei; Yan, Xiaole; He, Zaiqian; Ji, Jianlong; Hu, Jie; Li, Gang; Lian, Kun; Zhang, Wendong
Abstract : Top-down etching synthesis of α-Fe2 O3 concave and hollow nanocrystals. Abstract : In this work, uniform single-crystalline α-Fe2 O3 concave and hollow nanocrystals have been synthesized by a facile top-down etching method. Phosphate ions were employed as an etching agent to etch pristine icositetrahedra along their [006] direction in a top-down manner. The etched Fe2 O3 concave and hollow nanocrystals exhibit a much larger specific surface area (SSA) and more edges, corners and rough structures (hot spots) on the crystal surface compared to their mother crystal, thus serving as the possible origin of their comparative photocatalytic activities in the degradation of cationic dye Rhodamine B. These characteristics make them promising candidates as catalysts and sensing materials.